Beneficiation of the Nechalacho rare earth deposit. Part 1: Gravity and magnetic separation. (December 2016) - Jordens, Adam; Marion, Chris; Langlois, Ray; Grammatikopoulos, Tassos; Rowson, Neil A.; Waters, Kristian E.
Highlights: Coarse size fraction in feed enriched in heavy REE minerals (zircon) after grinding. Centrifugal gravity concentrators successfully concentrate high specific gravity REE minerals. Highest REE grade produced using Knelson and low intensity magnetic drum separator. Abstract: The beneficiation of rare earth element (REE) minerals may include many different beneficiation unit operations, but the final process choice typically depends on the inherent mineral characteristics. The Nechalacho REE deposit contains multiple low specific gravity, diamagnetic silicate gangue minerals (predominantly feldspars and quartz) and high specific gravity, iron oxide minerals (magnetite and hematite). The valuable REE minerals (REM) in the deposit consist of a variety of relatively high specific gravity, paramagnetic minerals. A process has been proposed to concentrate the value REM through a combination of gravity (rejecting silicate gangue) and magnetic (rejecting iron oxide gangue) separation steps prior to froth flotation. This work employed a laboratory-scale process including two different gravity separation steps (Knelson and Falcon centrifugal concentrators) followed by a series of varying intensity wet drum magnetic separation steps as well as dry induced roll magnetic separation and wet high intensity magnetic separation steps. The resultant fractions have been characterized by XRD, ICP-MS, and QEMSCAN to identify the optimum fraction for downstream flotation separation. The combination of a Knelson Concentrator with low intensity wet drum magnetic separation was found to efficiently concentrate REM while also rejecting high specific gravity iron oxide minerals. A novel finding from this study is the concentration of heavy REE-bearing zircon into coarse size fractions after grinding.